2021
DOI: 10.1016/j.jhazmat.2020.123496
|View full text |Cite
|
Sign up to set email alerts
|

A review of microplastics aggregation in aquatic environment: Influence factors, analytical methods, and environmental implications

Abstract: The aggregation of MPs in real aquatic environment is far from fully understood.  Sampling and analyzing methods for studying MP aggregation were summarized. Influence factors and environmental implications of MP aggregation were reviewed. MP aggregation in the field and their temporal stability deserve extensive research. Laboratory studies should use MPs representing those in real aquatic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(88 citation statements)
references
References 156 publications
(353 reference statements)
1
85
0
2
Order By: Relevance
“…This pattern is repeated in both long term and short term, and it portrays renewable energy consumption as a good measure to mitigate the environmental performance. This finding is in consonance with the findings from studies of (Kirikaleli and Adebayo, 2020;Shafiei and Salim, 2014;Wang, et al 2021;Khan et al 2020). Furthermore, Wald test is adopted in this present study for the purpose of unfolding the long run asymmetric interaction and its significance.…”
Section: Descriptive Statistics and Unit Root Testssupporting
confidence: 92%
“…This pattern is repeated in both long term and short term, and it portrays renewable energy consumption as a good measure to mitigate the environmental performance. This finding is in consonance with the findings from studies of (Kirikaleli and Adebayo, 2020;Shafiei and Salim, 2014;Wang, et al 2021;Khan et al 2020). Furthermore, Wald test is adopted in this present study for the purpose of unfolding the long run asymmetric interaction and its significance.…”
Section: Descriptive Statistics and Unit Root Testssupporting
confidence: 92%
“…Researchers collected the MP particles produced by the contact between the tire and the ground through a simulator (Kreider et al, 2010) and found that some of the MPs/NPs will enter the sewage and finally deposit and accumulate in the soil (Kole et al, 2017). As shown in Table 1, the MP content of tire powder (≤5 mm) entering the soil through atmospheric deposition exceeds 3 tons every year in France (Dris et al, 2016 (Wang et al, 2021b). Many studies have shown that the homo-aggregation of MPs/NPs can be described by the DLVO theory (Cai et al, 2018;Wang et al, 2021b).…”
Section: Roadside Litter and Car Tiresmentioning
confidence: 99%
“…As shown in Table 1, the MP content of tire powder (≤5 mm) entering the soil through atmospheric deposition exceeds 3 tons every year in France (Dris et al, 2016 (Wang et al, 2021b). Many studies have shown that the homo-aggregation of MPs/NPs can be described by the DLVO theory (Cai et al, 2018;Wang et al, 2021b). The classic DLVO assumes that the interaction force between particles includes van der Waals force and electrostatic force, which can predict the aggregation behaviour of MPs/ NPs (Cai et al, 2018).…”
Section: Roadside Litter and Car Tiresmentioning
confidence: 99%
“…Several approaches have been adapted to decontaminate polluted aquatic environments from HMs and organic pollutants (Ajiboye et al 2021) using techniques such as biochar , nano zero valent iron (Sliječpević et al 2021), and clays (Elshazly et al 2019). Other pollutants may cause serious threats to human health and ecosystems when they reach aquatic environments, including nanoparticles (Turan et al 2019;Souza et al 2021), antibiotics Xu et al 2021), microplastics (Ma et al 2020;Tang et al 2020;Pan et al 2021;Wang et al 2021), bisphenols Šauer et al 2021), retinoic acids (Yeung et al 2020), perfluoroalkylated acids (Groffen et al 2021), heavy metals (Aitta et al 2019;Karaouzas et al 2021), personal care products Lu et al 2021), antineoplastic agents (Yadav et al 2021) and COVID-19 (Kumar et al 2020a;Steffan et al 2020;Lachrich et al 2021). On the other hand, during lockdowns to combat COVID-19, the quality of surface water (Yunus et al 2020) and air (Guatam, 2020) are expected to improve.…”
Section: Aquatic Environments and Their Pollutionmentioning
confidence: 99%